2018
DOI: 10.1177/0022042618812398
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Strain and the Use of Nonmedical Prescription Drugs Among College Students

Abstract: The study of nonmedical prescription drug use (NMPDU) on college campuses is of importance, as college students tend to engage in NMPDU more often than their same-age peers not attending college. Typical correlates of NMPDU include need for alertness, perception of peer use, desire to get high, and use of other drugs including alcohol and marijuana. Few studies have explored the relationship between strain, depression, and NMPDU among college students. Using general strain theory as the theoretical framework, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 55 publications
(136 reference statements)
1
9
0
Order By: Relevance
“…In short, instrumental use is not uncommon among college students. Following from these apparent academic-related motives, several studies have demonstrated the applicability of general strain theory (Agnew, 2006) as it relates to NMPSU among college students (Ford & Schroeder, 2009; Maahs et al, 2016; Norman & Ford, 2018; Pate & Bolin, 2018; Prosek et al, 2018). General strain theory is an individualized extension of the macro-level theory developed initially by Merton (1938), which focuses on coping with the disjunction between the desire to achieve goals and a lack of access to the means necessary to do so.…”
Section: Nonmedical Prescription Stimulant Use By College Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In short, instrumental use is not uncommon among college students. Following from these apparent academic-related motives, several studies have demonstrated the applicability of general strain theory (Agnew, 2006) as it relates to NMPSU among college students (Ford & Schroeder, 2009; Maahs et al, 2016; Norman & Ford, 2018; Pate & Bolin, 2018; Prosek et al, 2018). General strain theory is an individualized extension of the macro-level theory developed initially by Merton (1938), which focuses on coping with the disjunction between the desire to achieve goals and a lack of access to the means necessary to do so.…”
Section: Nonmedical Prescription Stimulant Use By College Studentsmentioning
confidence: 99%
“…According to Agnew (2006), criminal coping is most likely to occur when strain leads to or coincides with negative affective states, such as anger, anxiety, fear, or depression. College students potentially experience a variety of strains from myriad sources directly and indirectly related to academic demands and performance (Pate & Bolin, 2018). Furthermore, these strains have been shown to be related to negative affective states (primarily depression) which, in turn, may increase the risk of substance use in general (Abraham & Fava, 1999; Davis et al, 2008; Zullig & Divin, 2012) and NMPSU specifically (Ford & Schroeder, 2009; Maahs et al, 2016; Pate & Bolin, 2018; Teter et al, 2010).…”
Section: Nonmedical Prescription Stimulant Use By College Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies that focus on college women and strain theory are rare, the extant literature has often found a relationship between strain and substance use as a coping mechanism. A study set in the southeast of the United States found that strain theory is associated with increased use of two types of prescription drugs although not with stimulants (Pate & Bolin, 2019). However, Peck et al (2018) found that young women reported greater depression but also less substance use than men when controlling for depression.…”
Section: Discussionmentioning
confidence: 99%
“…These authors argued that additional gender‐specific studies will be needed to clarify the relationship between gender, strain, and substance use. Pate and Bolin (2019) cautioned university officials to proceed cautiously with programming changes until we better understand the relationship between strain and substance use. Because studies have sometimes come to conflicting conclusions about the effect of strain on college women's substance use habits, additional work will be needed to reach a more confident conclusion.…”
Section: Discussionmentioning
confidence: 99%